Case Report: Eltrombopag in mosaic and gene therapy-treated patients with Fanconi anemia - Josune Zubicaray; June Iriondo; Elena Sebastián; Alejandro Sanz; Paula Rio; Jean Soulier; Sonsoles San Román; José J. Uriz; Susana Navarro; Eileen Nicoletti; Juan A. Bueren; Jonathan D. Schwartz; et al. (Frontiers in Pediatrics)
Fanconi anemia (FA) constitutes the most common of the inherited bone marrow failure syndromes, a group of rare heterogeneous disorders characterized by cytopenia, predisposition to hematologic and solid malignancies and diverse clinical features. Currently, the only available hematopoietic curative treatment for bone marrow failure is an allogeneic hematopoietic stem cell transplantation (HSCT), although gene therapy has demonstrated evidence of efficacy and substantially reduced toxicity. It has been demonstrated that eltrombopag stimulates trilineage hematopoiesis in aplastic anemia, and preclinical studies suggest it promotes DNA repair in FA hematopoietic stem cells (HSCs). Herein, we report the experience with eltrombopag in a patient misdiagnosed with aplastic anemia and subsequently determined to have FA mosaicism and in two FA patients who previously received gene therapy but who were infused with very low numbers of gene-corrected HSCs. Strikingly, the patient with somatic mosaicism achieved transfusion independence and averted HSCT, and the gene-therapy patients showed a marked increase of corrected cells during treatment.